(untitled) (Revista Horizontes de Linguistica Aplicada, 2018)
Digital Stories (DSs) have been developed and used for various purposes. This article presents a reflection on their use for L2 instruction, focusing on some approaches to sustain their use, as well as on an investigation on the development process, specifically on a brief review of literature in the area of DS development and on a description of the perceptions DS developers have as to the development process, with data collected with members of a laboratory for educational technology. Thus, a combination of perspectives on DS development is provided, so as to assist their use, receptively and productively, in the realm of applied linguistics, specifically for L2 instruction.